2021
DOI: 10.1101/2021.08.01.21261455
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-trait genome-wide association study identifies novel endometrial cancer risk loci that are associated with obesity or female testosterone levels

Abstract: We have performed genetic correlation and Mendelian randomization analyses using publicly available genome-wide association study (GWAS) data to identify endometrial cancer risk factors. These and previously established risk factors of endometrial cancer were then included in a multi-trait Bayesian GWAS analysis to detect endometrial cancer susceptibility variants, identifying three novel loci (7q22.1, 8q24.3 and 16q12.2); two of which were replicated in an independent endometrial cancer GWAS dataset. These lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“… 9 A major limitation of this and other genome-wide association study (GWAS) that have reported genetic loci for oestrogen production in postmenopausal women has been the use of immunoassays that lack precision, accuracy and specificity for the measurement of oestradiol. 9 , 10 , 11 , 12 , 13 , 14 For example, serum oestradiol, measured by immunoassay, was below the limit of detection in over 92% of postmenopausal women included in two GWAS that employed UK Biobank (UKBB) data. 10 , 11 Hence, analyses were limited to a very small, exceptional subset of women with inexplicably high oestradiol levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 A major limitation of this and other genome-wide association study (GWAS) that have reported genetic loci for oestrogen production in postmenopausal women has been the use of immunoassays that lack precision, accuracy and specificity for the measurement of oestradiol. 9 , 10 , 11 , 12 , 13 , 14 For example, serum oestradiol, measured by immunoassay, was below the limit of detection in over 92% of postmenopausal women included in two GWAS that employed UK Biobank (UKBB) data. 10 , 11 Hence, analyses were limited to a very small, exceptional subset of women with inexplicably high oestradiol levels.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, reported associations between blood testosterone and endometrial cancer GWAS are based on immunoassays known to lack precision, and hence reliability in women, 15 , 16 such that the findings should be considered uncertain. Other limitations include crude estimations of menopausal status 10 , 11 , 12 , 13 and that none of the aforementioned studies excluded women taking anti-oestrogens, anti-androgens therapy, or systemic glucocorticoids which modify blood oestradiol concentrations, thereby not representing women's authentic genetic profiles.…”
Section: Introductionmentioning
confidence: 99%